The status of sparrows in Lesotho, Southern Africa - Kopij, Grzegorz (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
There are three "Passer" species in Lesotho: House Sparrow "P. domesticus", Cape Sparrow "P. melanurus", and Grey-headed Sparrow "P. diffusus". The House Sparrow is an introduced species, recorded first in Lesotho in 1954.Today, all three species are very numerous (as dominants or subdominants) in urban and rural areas in all ecozones in the country.
Keywords: House Sparrow, "Passer domesticus"; Cape Sparrow "P. melanurus"; Grey?headed Sparrow "P. diffusus"; distribution; abundance; Drakensberg; Lesotho